USULAN RANCANGAN SISTEM USAHA WARALABA PADA RUMAH MAKAN SAWAYAKA SUSHI - Tamrin Tajuddin; Aprisa Rian Histiarini; Asih Ahistasari; Muhammad Rizky Hamunta (Universitas Muhammadiyah Sorong, 2022)
Franchise is a business activity using the method of granting licenses, trademarks, copyrights, or patents from the franchisor to the franchisee. Sawayaka Sushi is a franchise business that offers Japanese food products. Sawayaka Sushi is currently incomplete and does not cover all activities at Sawayaka Sushi. The restaurant owner has plans to expand his business by applying the improved franchise system to the new Sawayaka Sushi restaurant. The system that will be used is a franchise system that matches the Sawayaka Sushi restaurant. Therefore, the old Sawayaka Sushi business system will be evaluated and with this evaluation a new system will be created and can be proposed as a franchise business system at the Sawayaka Sushi restaurant. To find out whether Sawayaka Sushi's business is eligible to become a franchise or not, a franchisability study is used, namely from a qualitative and quantitative perspective. In the marketing strategy used SWOT analysis. The results obtained based on the business feasibility aspect show that the Sawayaka Sushi business can be said to be feasible. The payback period of the Sawayaka Sushi franchise is 2 years 7 months, the NPV generates a positive value of IDR 57,639,635. Internal Rate of Return (IRR) of 28.316% is declared acceptable.